Hybrid theatre: the combination of stage and digital space - Balytska, I. (ХДАК, 2026)
Today theatre is going through a very interesting period. We are used to thinking that theatre is a stage and an audience hall, and that this was the only space for communication between the actor and the audience. Now we have another space — the digital one. Because of this, a new concept has appeared: hybrid theatre. In this kind of theatre, live performance is combined with online formats, video projection, and augmented reality. Hybrid theatre is a modern form of theatrical art in which traditional stage elements (acting, scenery, light, and sound) are combined with digital, multimedia, or interactive technologies.
Keywords: гібридний театр; цифрові технології в театрі; digital technologies in theater